Optimisation of telephone triage of callers with symptoms suggestive of acute cardiovascular disease in out-of-hours primary care: observational design of the Safety First study. Issue 7 (1st July 2019) - Erkelens, Daphne CA; Wouters, Loes TCM; Zwart, Dorien LM; Damoiseaux, Roger AMJ; De Groot, Esther; Hoes, Arno W; Rutten, Frans H
Abstract : Introduction: In the Netherlands, the 'Netherlands Triage Standard' (NTS) is frequently used as digital decision support system for telephone triage at out-of-hours services in primary care (OHS-PC). The aim of the NTS is to guarantee accessible, efficient and safe care. However, there are indications that current triage is inefficient, with overestimation of urgency, notably in suspected acute cardiovascular disease. In addition, in primary care settings the NTS has only been validated against surrogate markers, and diagnostic accuracy with clinical outcomes as the reference is unknown. In the Safety First study, we address this gap in knowledge by describing, understanding and improving the diagnostic process and urgency allocation in callers with symptoms suggestive of acute cardiovascular disease, in order to improve both efficiency and safety of telephone triage in this domain. Methods and analysis: An observational study in which 3000 telephone triage recordings (period 2014–2016) will be analysed. Information is collected from the recordings including caller and symptom characteristics and urgency allocation. The callers' own general practitioners are contacted for the final diagnosis of each contact. We included recordings of callers with symptoms suggestive of acute coronary syndrome (ACS) or transient ischaemic attack (TIA)/stroke. With univariable and multivariable logistic regression analyses the diagnostic accuracy of caller and symptom characteristics will be analysed in terms of predictive values with urgency level, and ACS and TIA/stroke as outcomes, respectively. To further improve our understanding of the triage process at OHS-PC, we will carry out additional studies applying both quantitative and qualitative methods: (i) case-control study on serious adverse events (SAE), (ii) conversation analysis study and (iii) interview study with triage nurses. Ethics and dissemination: The Medical Ethics Committee Utrecht, the Netherlands endorsed this study (National Trial Register identification: NTR7331). Results will be disseminated at scientific conferences, regional educational sessions and publication in peer-reviewed journals.